Protection of cell membrane of buffalo spermatozoa during cryopreservation - SHABAD, RAM; SAXENA, V B; GUPTA, H P (The Indian Journal of Animal Reproduction, 2023)
Cell membrane of buffalo spermatozoa was substantially damaged in the egg yolk tris dilutor during cryopreservation asevidenced by greater release of transaminases and dehydrogenases enzymes. Insulin and foetal calf serum were found to protect thesperm cell membrane as evinced by reduced leakage of these enzymes and imporved level of motile, live and normal spermatozoaduring cryopreservation.
Keywords: Buffalo; spermatozoa; cryopreservation; additives